Effect of Sarecycline on the Acne Symptom and Impact Scale and Concerns in Moderate-to-Severe Truncal Acne in Open-Label Pilot Study - Angela Yen Moore; Kara Hurley; Stephen Andrew Moore; Luke Moore; Ilana Zago (Antibiotics, 2023)
Truncal acne is common, and the psychosocial burden may be underestimated as patients most often complain of facial acne. The Acne Symptom and Impact Scale (ASIS) is a 17-item patient-reported outcome (PRO) measure designed to assess the signs and impacts of acne vulgaris. ASIS has previously been validated in a prospective, non-interventional study as a reliable PRO instrument for facial acne. In a pilot study, ASIS, and an additional 10 new questions that focused on the concerns of patients (ASIS-C), were given to 10 patients with moderate-to-severe truncal acne vulgaris who received 3 months of monotherapy with oral sarecycline, a narrow-spectrum tetracycline-class antibiotic. ASIS-C questionnaires were also given to 10 acne-free control subjects. Average ASIS-C answers decreased by 4% for Signs, 15% for Impact, and 16% for Concerns in the 10 patients, with greater decreases of 5% for Signs, 20% for Impact, and 19% for Concerns in the 60% of patients whose truncal acne was clear or almost clear after 12 weeks of sarecycline treatment. In this study, sarecycline was effective in reducing the psychosocial burden associated with truncal acne based on the ASIS-C PRO measures.